Postindustrial Architecture, Dynamic Complexity and the Emerging Principles of Strategic Design - Bachman, Leonard (Enquiry The ARCC Journal for Architectural Research, 2007)
The transition from industrial era society to postindustrial society has shifted architecture away from being a predominantly cultural activity, one that is primarily focused on the physical attributes of a design. The newer architectural orientation leans more toward social ideals and strategic missions. These two perspectives have always coexisted in the discipline and critique of architecture, but the traditional subjugation of strategic concerns is eroding. The two aspects should now be considered in a more explicitly unified and mindful way. In that sense, the transition is not between two factions of practitioners with different philosophies, but between two aspects of thought balanced in some manner by each architect. The ultimate intentions of this paper are first to examine the forces of postindustrial change and then to outline a set of principles which establish strategic design as an architectural activity tantamount to, compatible with, and discursively engaged by physical design.